PELATIHAN INOVASI PENGEMBANGAN PRODUK KAUDAFA (TINJAUAN PRODUK UMKM LOKAL) - Maulana, Said Akhmad; Noveri, Edis Anggrea; Talia; Sanjaya, Dimas (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Innovative product development training serves as a strategic effort to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) that utilize local resource potential. This article discusses a product innovation training program implemented for KAUDAFA MSME, which processes moringa leaves (Moringa oleifera) as the main ingredient in food and beverage products in Teluk Limau Village, Parittiga District, West Bangka Regency. The primary goal of this training is to improve product quality through innovations in processing techniques, packaging design, and digital marketing strategies to expand market reach. This study employs a qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that the participants' capacity to develop moringa-based innovative products has significantly improved, which in turn contributes to the sustainable economic development of the local community.